2010
DOI: 10.1103/physreve.81.046203
|View full text |Cite
|
Sign up to set email alerts
|

Chimera and globally clustered chimera: Impact of time delay

Abstract: Following a short report of our preliminary results [Phys. Rev. E 79, 055203(R) (2009)], we present a more detailed study of the effects of coupling delay in diffusively coupled phase oscillator populations. We find that coupling delay induces chimera and globally clustered chimera (GCC) states in delay coupled populations. We show the existence of multi-clustered states that act as link between the chimera and the GCC states. A stable GCC state goes through a variety of GCC states, namely periodic, aperiodic,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The sparsity of induced by may yield coexisting synchronized and desynchronized groups within the network, which are often labelled chimera states in the study of phase oscillator systems. It has been found that they crucially depend on the combination of coupling strengths and phase shifts [45], [54], [55] (or delays [56]), confirming that there has to be a specific matching of coupling and delays for synchronization to occur.…”
Section: Discussionmentioning
confidence: 94%
“…The sparsity of induced by may yield coexisting synchronized and desynchronized groups within the network, which are often labelled chimera states in the study of phase oscillator systems. It has been found that they crucially depend on the combination of coupling strengths and phase shifts [45], [54], [55] (or delays [56]), confirming that there has to be a specific matching of coupling and delays for synchronization to occur.…”
Section: Discussionmentioning
confidence: 94%
“…Complex chimera-like synchronization behaviour, involving the unstable formation of synchronized and desynchronized coalitions of oscillators driven by transitions between metastable states, has been demonstrated in phase-lagged Kuramoto oscillator networks under differing topologies. 15,16 While the continuous exchange of phase information between network participants present in these models is an accurate abstraction of many systems, the detailed operation of the mammalian brain, the all-or-nothing "action potentials" sent over the synapses connecting neurons, is better described by the exchange of a series of discrete events.…”
Section: Introductionmentioning
confidence: 99%
“…An ensemble of coupled oscillators is a veritable black box exhibiting a plethora of complex cooperative dynamical behaviors mimicking several real world phenomena [1,2,3,4]. Chimera state is such an intriguing emerging behavior that has been identified in an ensemble of identical oscillators with non-local coupling [5,6,7,8,9,10,11,12,13,14,15]. Since its identification, the notion of chimera has provoked a flurry of intense investigations because of the surprising fact that such an ensemble splits into two dynamically distinct domains, wherein all the oscillators evolve in synchrony in the coherent domain, while the oscillators in the incoherent domain evolve in asynchrony [16,17,18].…”
Section: Introductionmentioning
confidence: 99%